BOSHLANG‘ICH SINFLARDA KITOBXONLIK TADBIRLARI - Zоkirjоn Isaqоv, Niyozmatov Abdullajon, Niуоzmatоva Umidaxоn (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Abstract The article discusses the methodology of conducting reading activities in primary classes, and gives the necessary recommendations for its organization.